Morfologia da bolsa cloacal de emas (Rhea americana americana LINNAEUS, 1758) - Oliveira, Radan Elvis Matias de (2017)
The cloacal bursa is the responsible organ of the birds for the maturation and transfer of lymphocytes to other tissues. Despite the importance of this organ in the immunological mechanisms of these animals, there is little information on the development and ultrastructure in young greater rhea. The objective of this study was to describe macroscopy, microscopy, ultrastructure and arterial vascularization of cloacal bursa of young greater rhea. In this study, 26 animals of both sexes (8 males and 18 females) were used, 20 of which were animals for macroscopy and arterial vascularization, and the six for light microscopy, transmission electron microscopy and scanning electron microscopy. The greater rhea cloacal bursa is a hollow organ, rounded, slightly flattened, pinkish color and with pleated inner mucosa, located dorsally to the cloaca, with whom it communicates through an ostium. It was verified that, irrigation of the cloacal sac occurs from terminal branches of the abdominal aorta, such as the right and left internal iliac arteries and the caudal mesenteric arteries. Left and right internal iliac arteries originated the right and left internal pudendal arteries, which in turn gave rise to right and left bursocloacal and cloacal arteries in all animals analyzed. Microscopically, the cloacal sac of the emu presented, at all ages, the pleated internal mucosa composed of lymphoid lobes of various sizes and organized as alveolar structure, presenting two types of lining epithelia, the bundle lobe epithelium, the simple squamous type and interlobular epithelium, corresponding to the columnar stratification. These lobes consisted of cortical zone, corticomedular zone and medullar zone. Arranged in these lobes, the existence of lymphocytes of various sizes, lymphoblasts, blood capillaries, epithelial reticular cells and macrophages were verified by transmission microscopy. In the scanning, the surface of the mucosa of the bursal lobes presented polygonal projections, with the presence of small microvilli on the whole surface. It was concluded that the cloacal bursa of the young greater rhea was presented as a distinct structure of the cloaca, with varied size as a function of age, and also, its development was observed from the sixth week of life